Мінітексти-жарти в журналі "Жінка" (на матеріалі видання 2011 – 2014 років) - Мамич, М. (Культура слова, 2019)
У статті представлено лексико-граматичні та асоціативно-
семантичні способи вербалізації основних ціннісно-аксіологічних
концептів – жінка, чоловік, розум, дитина. Медіаконтент сучасного
журналу «Жінка» схарактеризовано як контейнер, який охоплює
універсальну інформацію, зокрема емоційну, жартівливу. Відзначено
важливість уваги до анекдотів як до побутових, літературних
історій, які відбивають ключові концепції взаємин людей, але самі при
цьому не використовуються для створення цих концепцій. Зауважено
про роль мінітекстів жартів як засобу психологічного і соціального
розвантаження, активізації позитивного світосприймання людини.
Анекдоти як писемно відтворені усні оповідні жанри доносять
до цільової аудиторії в художній образній формі певні ціннісні
домінанти, на які мають орієнтуватися сучасні українці, а
також гендерні аспекти мовно-культурної діяльності у спільноті,
а у цілому – відбивають інформаційно-комунікативну культуру
спільноти. The article presents lexical-grammatical and associative-semantic
methods of verbalization of basic value-axiological concepts - woman,
man, mind, child. The mediacontent of the modern magazine “Zinka” is
characterized as a container that covers universal information, including
emotional, playful one. The importance of attention to anecdotes is noted
as to everyday, literary stories, which reflect key concepts of human
relationships, but are not used to create these concepts. The role of minitexts
of jokes as a means of psychological and social unloading, activation
of a positive world-view of a person is noted. Anecdotes as oral narrative
genres are reproduced in written and bring to the target audience in the
artistic form certain value dominants, which contemporary Ukrainians
should focus on, as well as gender aspects of linguo-cultural activity in the
community, and in general, reflect informative-communication culture of
community.
All text material is analyzed with attention to the following linguistic
means of comism creation: the contrast of direct and figurative meaning of
the word and phraseological reversal, the contrast of high and low, literary
and colloquial in stylistic semantics of words and phraseological reversals,
pun, semantic alogisms of homonyms, synonyms and paronims.
Particular attention is paid to the functions of precedent name in literary
anecdotes. It is noted that in Ukrainian laughter culture the appellation to
a precedent phenomenon is traditional, which serves as the undisputed
authority, because for a long time a certain image of a leader has been
formed in society, template ideas about it are finished, which gives the
impression of the authenticity of the situation being played. It is shown
that in such anecdotes and jokes the precedent name acquires interactive
features, and the public image of the so-called media persona is updated
every time, activating the linguocultural memory of the audience of
listeners-readers.